Epidemiological and Molecular Investigations on Salmonella Responsible for Gastrointestinal Infections in the Southwest of Shanghai From 1998 to 2017 - Qi, Xulin; Li, Pei; Xu, Xiaogang; Yuan, Yiqun; Bu, Shurui; Lin, Dongfang (Frontiers in Microbiology, 2019)
Purpose: To investigate the characteristics of gastrointestinal infections in Southwest Shanghai. Methods: Clinical and epidemiological characteristics of patients with Salmonella infections between 1998 and 2017 admitted to the Jinshan Hospital in the Southwest of Shanghai were retrospectively analyzed. A total of 565 isolated Salmonella strains were classified by serotyping and pulsed field gel electrophoresis (PFGE). Results: From 1998 to 2006, diarrhea was mainly caused by Vibrio parahaemolyticus followed by Shigella and Salmonella. From 2007 to 2010, Vibrio parahaemolyticus infection was the major cause of diarrhea followed by Salmonella and Shigella. From 2011 to 2017, Salmonella infections became the main cause of diarrhea after Vibrio parahaemolyticus. Salmonella infections increased from 2006 on and peaked between May and October, accounting for 82.48% of yearly infections. Patients with Salmonella infections (90.5%) had a history of eating unclean food, abdominal pain (58.05%), diarrhea ≥ 5 times a day (50.44%), moderate fever (24.96%) and increased fecal leukocytes (41.42%). From 1998 to 2017, infected specimens from clinical cases were dominated by Salmonella enterica serovar Typhimurium (S. Typhimurium) (21.59%) followed by Salmonella enterica serovar Enteritis (S. Enteritidis) (16.81%), Salmonella enterica serotype London (6.55%) and Salmonella group B (13.10%). Other species included Salmonella enterica serovar Thompson, Salmonella enterica serovar Saintpaul, Salmonella group D, Salmonella group C, Salmonella enterica serovar Choleraesuis and Salmonella enterica serovar Aberdeen. The PFGE classification of Salmonella serovars in 2008-2017 demonstrated that S. Enteritidis had 9 PFGE banding patterns and S. Typhimurium 16 with varying degrees of similarity among S. Enteritidis and S. Typhimurium. The results of antibiotic susceptibility tests for the 330 Salmonella strains revealed that fosfomycin had the highest sensitivity rate (97.5%) followed by levofloxacin and ceftriaxone (81%), and ampicillin/sulbactam (78.2%). The resistance to piperacillin and ciprofloxacin was 60.9% and 50.61%, respectively. Conclusions: The features of onset, epidemiological characteristics and molecular subtyping of Salmonella were conducive to clinical diagnosis, rational use of antibiotics and improved therapeutic efficacy.